2010
DOI: 10.1177/0961203309356458
|View full text |Cite
|
Sign up to set email alerts
|

Cryptococcosis in systemic lupus erythematosus: a series of six cases

Abstract: The aims of this study were to describe the clinical features of patients with systemic lupus erythematosus (SLE) who developed cryptococcal infection and ascertain their outcomes when treated with glucocorticoids and immunosuppressive agents in conjunction with long-term maintenance antifungal therapy. Six cases of cryptococcal infection in SLE were reviewed retrospectively. The mean age at the time of infection was 26.3 (11.7) years. Three patients had active SLE and all were receiving glucocorticoids [media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 10 publications
0
15
1
Order By: Relevance
“…HIV infection is the major risk factor for cryptococcosis. Other populations at risk include solid-organ and hematological stem cell transplant recipients; patients with malignancies 26,27 ; those receiving immunomodulating and biologic agents, including patients treated for systemic lupus erythematosus (SLE), 28,29 sarcoidosis, 30 and rheumatoid arthritis 31 ; and individuals with CD4 lymphopaenia. 32,33 These risk factors have been described in both C. neoformans and C. gattii infections.…”
Section: Host Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…HIV infection is the major risk factor for cryptococcosis. Other populations at risk include solid-organ and hematological stem cell transplant recipients; patients with malignancies 26,27 ; those receiving immunomodulating and biologic agents, including patients treated for systemic lupus erythematosus (SLE), 28,29 sarcoidosis, 30 and rheumatoid arthritis 31 ; and individuals with CD4 lymphopaenia. 32,33 These risk factors have been described in both C. neoformans and C. gattii infections.…”
Section: Host Risk Factorsmentioning
confidence: 99%
“…The impact of HIV on the immune response to cryptococcosis is also reviewed by Chang et al 54 Complement and mannose-binding lectin deficiency, impaired chemotaxis and phagocytosis of macrophages and polymorphonuclear cells, and abnormal T-cell-mediated cytotoxicity associated with SLE and glucocorticoid use contribute to the pathogenesis of cryptococcosis. 29…”
Section: Immunopathogenesis Of Cryptococcosismentioning
confidence: 99%
“…1 The most common risk factors for infection in SLE patients are the use of high-dose corticosteroids, antibiotics exposure, 2 high SLE activity and intrinsic disorders of cell-mediated immunity. 3 Moreover, as SLE is a systemic disease, ~20%–70% of SLE patients develop central nervous system (CNS) damage due to autoimmune-mediated attack, 4 making the CNS susceptible to infection through impairment of the blood–brain barrier.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have revealed the propagules of C. neoformans and C. gattii floating in the air can be inhaled by human beings . Some people are resistant to the infectious propagules, but others unfortunately develop cryptococcosis . Transmission of cryptococcosis from human to human was rarely found .…”
Section: Introductionmentioning
confidence: 99%